Antibacterial Activity of Ethanol Extract of Spirulina platensis - Prayoga Pannindrya; Mega Safithri; Kustiariyah Tarman (IPB University, 2020)
Spirulina is a microalgae that has been widely used as various supplements and medicines because of its high nutritional content. The need for new antibacterial sources to solve the problem of antibiotic resistance, makes the potential of Spirulina as an antibacterial agent necessary to be researched. This study aims to analyze the antibacterial activity of ethanol extract of Spirulina platensis obtained from the Indonesian region against Staphylococcus aureus and Escherichia coli. Spirulina samples were macerated in ethanol solvent in a ratio of 1:10 (w / v). The antibacterial test used was the disc diffusion method with clindamycin positive control. Antibacterial test results showed that S. platensis in this study did not have antibacterial activity against E. coli and S. aureus.